Evaluation of Different Housing Typologies with a Design Pedagogy - Yildirim, Yalcin; Cakil, Elif Altas; Ersoy, Merve (Mdpi, 2025)
Design studios generally concentrate on some critical concerns of urban life to overcome, and housing is one of those. Rapid development and advanced technology increase the need for and problems with housing. Such concerns should be addressed in theory, practice, and pedagogy. This study assesses the sophomores' design output and their understanding of housing typologies based on real-world project sites to contribute to pedagogical aspects. Our study results show that students' villa typologies generally focus on specific social groups with central themes, including health and recreation, while apartment complex designs converge on community life, urban identity, and tranquility. Based on the survey, students were part of it; they had difficulty with the scale and site-related grading problems, while most wished to work on the other typology theme. This study eventually calls attention to housing problems based on the design students' perspectives on different residential typologies.
Keywords: housing; typology; pedagogy; studio